code mixing malay teks CODE MIXING IN NARRATIVE TEXT BRUNEI DARUSSALAM STUDENTS - Kim, Dong Hoon (Universitas Cokroaminoto Palopo, 2024)
This study aims to discuss the form of Indonesian and Malay code mixing in a collection of narrative texts of Malay students from Brunei Darussalam who took the fall semester at the Malay-Indonesian study program at Hankuk University of Foreign Studies Korea. The approach used in this study is qualitative with the content analysis method. The primary data in this study is a collection of narrative texts of Malay students from Brunei Darussalam who take the title about visits to tourist attractions in South Korea. Based on the results of this study, 16 forms of code mixing were found in Indonesian and Malay in the collection of student narrative texts with language code mixing forms such as the insertion of elements in the form of words and the insertion of elements in the form of phrases. The collection of narrative texts of Brunei Darussalam students, especially in terms of language use, still contains elements of absorption from the Malay language that developed from Indonesia, especially the Riau Malay language, this proves that there is a kinship between the Malay language and the Indonesian language.